Physicians’ Perspective of Telemedicine Regulating Guidelines and Ethical Aspects: A Saudi Experience - Dalia Yahia M. El Kheir; Sara S. Alnufaili; Raghad M. Alsaffar; Majd A. Assad; Zahra Z. Alkhalifah (International Journal of Telemedicine and Applications)
Background and Objective. The rapid emergence and evolution of digital technology have greatly improved the quality and accessibility of healthcare services worldwide. Nonetheless, the literature is scarce regarding the ethical and legal aspects of telemedicine and social media (SM) use in healthcare. Thus, this paper examines physicians’ perceptions about the use of telemedicine in patient care, their awareness of guidelines for health-related use of telemedicine, and their knowledge, attitude, and practice of the ethical and legal regulations governing the use of telemedicine in the healthcare context. Methods. This was an observational cross-sectional study conducted among physicians working at the College of Medicine, Imam Abdulrahman Bin Faisal University (IAU), and its affiliated academic tertiary hospital, King Fahad Hospital of the University (KFHU), Eastern province-KSA. Data were collected between August 2019 and March 2020 via a structured, pretested, self-administered questionnaire distributed to 220 eligible physicians at KFHU. A final sample of 101 physicians completed our survey. Collected data was coded and analysed using SPSS, and the results presented as frequencies, percentages, and summary statistics. Results. Among our respondents, 62 (61.4%) were males, 46 (45.5%) were in the age group of 35 to 44 years, and 62 (61.3%) were Saudi. Two-thirds of physicians (58 (57.4%)) use smart devices in healthcare delivery, and 51 (50.5%) are satisfied with this use. A minority (21 (20.8%)) knew about telemedicine guidelines, 8 (7.9%) had encountered legal issues related to telemedicine use, and 52 (51.5%) were doubtful about patients’ readiness for virtual care. Regarding physicians’ awareness of the ethical aspects regulating the use of social media and medical apps in patient care, only 44 (45.3%) were aware of the proper reporting system if they found accounts sharing unreliable information. Nevertheless, the majority (91 (92.9%)) agreed it is essential for healthcare providers to report such accounts. Concerning physicians’ awareness of the rules and regulations of online self-promotion, the majority of our respondents were unsure or unaware of such regulations (46 (45.6%) and 18 (17.8%)), respectively. Nonetheless, 67 (66.3%) of the physicians would not pay SM influencers to advertise for them. Conclusion. Two-thirds of our physicians use smart devices in healthcare delivery, with 1 in 13 having encountered related legal issues. Nonetheless, only a minority was aware of telemedicine use regulating guidelines, including physicians’ online self-promotion regulations. These results highlight the necessity of targeted physicians’ training on telemedicine use related guidelines, thereby ensuring the safety of both patients and healthcare professionals and the optimum utilization of online health-related interactions.